2011
DOI: 10.1159/000323908
|View full text |Cite
|
Sign up to set email alerts
|

Specific Tear IgE in Patients with Moderate-to-Severe Autumnal Allergic Conjunctivitis

Abstract: Background: Recently, a new commercial test for specific IgE based on immunochromatography (Immfast Check J1®) has been developed. We previously reported on the use of this kit for tear fluid samples during spring. In this study, we compared the level of specific IgE in tear fluid among patients with seasonal allergic conjunctivitis during spring or autumn and control subjects. Methods: A nonrandomized, cross-sectional study was conducted in patients with moderate-to-severe allergic conjunctivitis occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…[3][4][5][6][7][8] patients with spring and autumnal seasonal allergic conjunctivitis, and found that the positive rates of tear fluid were respectively 96.9% (62/64) and 86.5% (45/52) for cedar pollen IgE, 53.1% (34/64) and 96.2% (50/52) for D. pteronyssinusIgE, and 23.4% (15/64) and 25.0% (13/52) for cat epithelium/dander IgE. 10,11 For clinical evaluation of the severity of allergic conjunctivitis, conventional slit lamp examination is very important and the severity of conjunctivitis has been classified from the ocular findings on slit lamp examination in various studies. [12][13][14][15][16][17][18][19] Although the level of specific IgE in tear fluid can be a useful diagnostic indicator for seasonal allergic conjunctivitis, it is still unclear whether measurement of tear fluid IgE is helpful for assessing the severity of allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] patients with spring and autumnal seasonal allergic conjunctivitis, and found that the positive rates of tear fluid were respectively 96.9% (62/64) and 86.5% (45/52) for cedar pollen IgE, 53.1% (34/64) and 96.2% (50/52) for D. pteronyssinusIgE, and 23.4% (15/64) and 25.0% (13/52) for cat epithelium/dander IgE. 10,11 For clinical evaluation of the severity of allergic conjunctivitis, conventional slit lamp examination is very important and the severity of conjunctivitis has been classified from the ocular findings on slit lamp examination in various studies. [12][13][14][15][16][17][18][19] Although the level of specific IgE in tear fluid can be a useful diagnostic indicator for seasonal allergic conjunctivitis, it is still unclear whether measurement of tear fluid IgE is helpful for assessing the severity of allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that allergen-speci c IgE antibodies in tears were considered to be produced locally rather than the antibodies from serum [19,24,25]. We have reported that antigen sensitization likely to occur in conjunctiva in pollinosis, because positive rate of t-tIgE was signi cantly higher in patients with pollinosis than the positive rate of pollen-sIgE [19].…”
Section: Discussionmentioning
confidence: 87%
“…2) might suggest nasal symptoms derived from allergic rhinitis have an important clinical or pathophysiological role in the QOL of patients with ACD. There is a correlation between seasonal onset groups of ACD and season speci c antigens [24,25,[27][28][29]. It was reported that treatment of ACD improved the quality of life by reducing t-tIgE and clinical symptoms [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Mimura et al reported regarding the correlation between the t-tIgE score and s-sIgE levels against house dust mites and found that house dust mite allergens may be the primary cause of AC during autumn in Japan [ 20 ]. Despite these reports, the lack of significant difference of the total score of food-sIgE between the t-tIgE positive group and negative group suggests that food-induced AC might be induced by the different pathological mechanism involved in pollen-induced AC.…”
Section: Discussionmentioning
confidence: 99%